Cover Crop-Based, Organic Rotational No-Till Corn and Soybean Production Systems in the Mid-Atlantic United States - John M. Wallace (Agriculture, 2017)
Cover crop-based, organic rotational no-till (CCORNT) corn and soybean production is becoming a viable strategy for reducing tillage in organic annual grain systems in the mid-Atlantic, United States. This strategy relies on mechanical termination of cover crops with a roller-crimper and no-till planting corn and soybean into cover crop mulches. Here, we report on recent research that focuses on integrated approaches for crop, nutrient and pest management in CCORNT systems that consider system and regional constraints for adoption in the mid-Atlantic. Our research suggests that no-till planting soybean into roller-crimped cereal rye can produce consistent yields. However, constraints to fertility management have produced less consistent no-till corn yields. Our research shows that grass-legume mixtures can improve N-release synchrony with corn demand and also improve weed suppression. Integration of high-residue inter-row cultivation improves weed control consistency and may reduce reliance on optimizing cover crop biomass accumulation for weed suppression. System-specific strategies are needed to address volunteer cover crops in later rotational phases, which result from incomplete cover crop termination with the roller crimper. The paucity of adequate machinery for optimizing establishment of cash crops into thick residue mulch remains a major constraint on CCORNT adoption. Similarly, breeding efforts are needed to improve cover crop germplasm and develop regionally-adapted varieties.